Effectiveness of ultrasound-guided lumbar facet-joint injection technique: comparative study with fluoroscopy-guided technique - Ozturk, Sait; Ozturk, Yasar; Okcesiz, Izzet (Cukurova Univ, Fac Medicine, 2017)
Purpose: In this study we aimed to compare the feasibility, effectiveness and complication rates of ultrasound-guided lumbar facet-joint injections (FJI) in patients with fluoroscopy-guided technique. Material and Methods: Patients who were diagnosed with lumbar facet syndrome between the years of 20152016 were included in this retrospective study. Patients were divided into two subgroups: patients who underwent FJI with ultrasound-guided (US) and patients who underwent FJI with fluoroscopy-guided (FS). The age, gender, duration of complaints, number of applied facet joint injection and duration of intervention were recorded in both groups. In addition, visual analogue scale (VAS) and Modified Oswestry Disability Index (MODI) values were recorded just before the intervention and on the 1st, 7th, 30th and 90th days following the procedure in both groups and the results compared. Results: A total of 81 patients, 41 in the US group and 40 in the FS group, underwent FJI. The average duration of complaints in the US group was 12.2 months, which was 13.1 months in the FS group. The duration of the procedure was 4.2 minutes in the FS group, which was 4.1 minutes in the US group. In both groups, VAS and MODI values recorded at different periods before injection and after injection showed a significant decrease. Conclusion: Ultrasound-guided FJI technique is as effective as fluoroscopy-guided technique. Furthermore, the lack of exposure to radioactive radiation during the process is a significant advantage.
Keywords: Facet joint; medial branch; fluoroscopy; ultrasound; injection